Methodology of analysis and evaluation of websites 2.0. The case of the Andalusian Dioces - Jiménez Carreira, Manuel (2018)
he rapid cyberspace evolution and the volatility of both, websites as well as online media requires an ongoing education of the technique and study methods. We have developed a new model of analysis, unifying previous designs and completing it with a contrasted results validation system. We confront this query from a global perspective and in line with Web 2.0 and social media.For this we start from the Communication Model Website (WCM), developed by Juan Narbona, which analyzes websites using four pillars: content and services, technical instruments, promoters and visitors. This model, valid for Web 1.0, was updated by Daniel Arasa in the Online Communication Model (OCM), which adds a fifth pillar to contemplate social media taking into consideration social media. Also take into account we lean on a quantitative method measurement system the Sistema Articulado de Análisis de Cibermedios (SAAC), for further validation.